2023
DOI: 10.1038/s41551-023-01025-1
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of local inflammation via galectin-anchored indoleamine 2,3-dioxygenase

Abstract: The treatment of chronic inflammation with systemically administered anti-inflammatory treatments is associated with moderate-to-severe side effects, and the efficacy of locally administered drugs is short-lived. Here we show that inflammation can be locally suppressed by a fusion protein of the immunosuppressive enzyme indoleamine 2,3-dioxygenase 1 (IDO) and galectin-3 (Gal3). Gal3 anchors IDO to tissue, limiting the diffusion of IDO-Gal3 away from the injection site. In rodent models of endotoxin-induced inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…Also, the KYNU/IDO-TDO ratio demonstrated a significant increase in inflammatory diseases [ 25 ]. IDO promotes an anti-inflammatory environment in the skin by T-cell suppression and regulatory T-cell induction [ 50 ], which in turn reduces KYNU expression levels [ 25 ]. Therefore, this appears that inhibiting the IL-17 in an aptamer-treated group helps the modulation of an inflammatory milieu in the skin, thereby may affecting tryptophan metabolism through the IDO.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the KYNU/IDO-TDO ratio demonstrated a significant increase in inflammatory diseases [ 25 ]. IDO promotes an anti-inflammatory environment in the skin by T-cell suppression and regulatory T-cell induction [ 50 ], which in turn reduces KYNU expression levels [ 25 ]. Therefore, this appears that inhibiting the IL-17 in an aptamer-treated group helps the modulation of an inflammatory milieu in the skin, thereby may affecting tryptophan metabolism through the IDO.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a series of preclinical evaluations using ABLE in the imiquimod (IMQ)–induced psoriasis model ( 31 ). This model is widely used in in vivo research because of its clinical and histological similarities to human psoriasis, including characteristic symptoms such as desquamation, thickening of the epithelial structure, skin inflammation, and dysregulated host skin microbiota ( 32 ).…”
Section: Skin Disease Monitoring and Therapy With Ableunclassified
“… 9 , 10 High expression of IDO can also disrupt the function of inflammatory cells and reduce the levels of inflammatory cytokines. 11 , 12 Our previous research identified significantly increased levels of the plasma and urine levels of IDO in patients with early-stage CKD, and that these levels were also associated with inflammation due to CKD. 13 , 14 Therefore, measurement of IDO activity along with other indicators may allow the timely and accurate prediction of early CKD and CKD progression.…”
Section: Introductionmentioning
confidence: 95%